Preoperative and postoperative blood testosterone levels in patients with acromegaly: a prospective study - Zhang, Duoxing; Guo, Xiaopeng; Feng, Ming; Bao, Xinjie; Deng, Kan; Yao, Yong; Lian, Wei; Xing, Bing; Wang, Hanbi (Frontiers in Endocrinology, 2023)
Purpose To investigate the prevalence of low blood testosterone level (LTL) and its determinant factors among active male acromegaly patients, as well as the effect of surgery on LTL in male acromegaly patients. Methods A retrospective, single-center study focused on 252 male acromegaly patients aged 18 years–60 years diagnosed in the Peking Union Medical College Hospital from January 2015 to December 2018 was carried out. The measurements of preoperative and postoperative testosterone levels, serum growth hormone (GH), insulin-like growth factor 1 (IGF-1), and other clinical data were analyzed. Results Forty per cent of subjects included were diagnosed with LTL pre surgery. Patients were divided into normal testosterone level (NTL) and LTL groups based on their testosterone level. There were significant differences (p < 0.01) between groups in the presence of macroadenomas, invasion of the cavernous sinus, compression of the optic chiasm, and serum GH and prolactin levels pre surgery. Invasion of the cavernous sinus [odds ratio (OR) = 4.299; p = 0.000] and serum prolactin level (OR = 1.023, p = 0.001) were independent predictors of LTLs in male patients before surgical intervention. A total of 67.9% of LTL patients recovered during the follow-up, with a new-onset rate of 3.4%. Body mass index, invasion of the cavernous sinus, GH, IGF-1, and prolactin levels, the presence of a prolactin-secreting tumor, and recovery from acromegaly were significantly different (p < 0.05) in the NTL group and in the LTL group during the follow-up. The presence of a prolactin-secreting tumor (OR = 0.224; p = 0.001) and recovery from acromegaly (OR = 0.168; p = 0.006) were independent predictors of LTLs in male acromegaly patients during the follow-up. Conclusion The invasiveness of tumor and levels of blood prolactin are independent factors for LTLs before surgery, whereas GH and IGF-1 levels are not. Most male patients can recover from LTL after tumor restriction surgery: those who recover from acromegaly have a better chance of recovering from LTL.